Inhibitory effect of six herbal extracts on CYP2C8 enzyme activity in human liver microsomes. (May 2015) - Albassam, Ahmed A.; Mohamed, Mohamed-Eslam F.; Frye, Reginald F.
Abstract 1. Herbal supplements widely used in the US were screened for the potential to inhibit CYP2C8 activity in human liver microsomes. The herbal extracts screened were garlic, echinacea, saw palmetto, valerian, black cohosh and cranberry. N-desethylamodiaquine (DEAQ) and hydroxypioglitazone metabolite formation were used as indices of CYP2C8 activity. 2. All herbal extracts showed inhibition of CYP2C8 activity for at least one of three concentrations tested. A volume per dose index (VDI) was calculated to determine the volume in which a dose should be diluted to obtain IC50 equivalent concentration. Cranberry and saw palmetto had a VDI value >5.0 l per dose unit, suggesting a potential for interaction. 3. Inhibition curves were constructed and the IC50 (mean ± SE) values were 24.7 ± 2.7 μg/ml for cranberry and 15.4 ± 1.7 μg/ml for saw palmetto. 4. The results suggest a potential for cranberry or saw palmetto extracts to inhibit CYP2C8 activity. Clinical studies are needed to evaluate the significance of this interaction.